The The Effectiveness of Video-Based Instruction in Enhancing English Language Competency: Evidence from Dondaeng Upper Secondary School, Laos - Luangsombath, Soulichanh (Souphanouvong University Journal Multidisciplinary Research and Development, 2026)
The persistent reliance on traditional, textbook-centric methods in Lao secondary English as a Foreign Language (EFL) instruction often contributes to low student proficiency and a lack of authentic communicative competence, highlighting a critical pedagogical gap. This quasi-experimental study investigates the effectiveness of video materials in enhancing the English language competency of 60-year 6th students (n=30 control, n=30 experimental) at Dondaeng Upper Secondary School, grounded in principles of Multimedia Learning Theory and constructivism. The research objectives were: 1) to compare students' learning achievement between traditional textbook-based instruction and video-based instruction; 2) to assess students' English language competency development through video material utilization; and 3) to investigate students' opinions and perspectives on utilizing video materials. Students in the experimental group received instruction incorporating a structured three-stage (pre-, while-, post-listening) video methodology. Post-test results demonstrated that the experimental group achieved significantly greater learning achievement ( =8.87, SD=0.57) compared to the control group ( =7.50, SD=0.86), revealing a very large and statistically significant effect size (d 1.88, p < .001). Furthermore, the experimental group showed markedly superior overall language competency ( =9.40, SD=0.49) over the control group ( =7.77, SD=0.77), indicating an exceptionally large and statistically significant effect (d 2.51, p < .001). Student attitudes toward videos were overwhelmingly positive, citing enhanced motivation and the provision of authentic language context. This research confirms that strategically integrated, theoretically grounded video instruction provides a potent, accessible solution to enhance EFL outcomes, offering critical evidence for educational policy modernization and alignment with contemporary regional EFL standards.